Amplification of Mycoplasma haemofelis DNA by a PCR for point-of-care use. (January 2018) - Hawley, Jennifer; Yaaran, Tal; Maurice, Sarah; Lappin, Michael R.
We compared a qualitative in-clinic (IC)-PCR for the detection of Mycoplasma haemofelis DNA with the results of a commercial qualitative laboratory-based, conventional (c)PCR. In order to determine the specificity of both tests, Bartonella spp. samples were included. Forty-three previously tested blood samples with known PCR results for hemoplasmas and Bartonella spp. were selected. The samples were split between 2 laboratories. At the first laboratory, DNA was purified and run on 2 cPCR assays for the detection of hemoplasmas and Bartonella spp. At the second laboratory, DNA was purified using 2 purification protocols and both run in the IC-PCR assay. The cPCR results confirmed that 18 samples were positive for M. haemofelis, 5 for ' Candidatus M. haemominutum ', 8 for Bartonella henselae, 2 for Bartonella clarridgeiae, and 10 were negative for both genera. No mixed infections were observed. The IC-PCR assay for the detection of M. haemofelis had a sensitivity of 94.4% and specificity of 96%, when using the same DNA purification method as the first laboratory. Using the second purification method, the sensitivity of the IC-PCR assay was 77.8% and specificity was 96%. Bartonella species were not detected by the IC-PCR M. haemofelis assay. The IC-PCR assay decreased the amount of time to final result compared to a cPCR assay.